Financial Centre Bias: Another Puzzling Anomaly in the IPO Market? - Wójcik, D (School of Geography and Environment (University of Oxford), 2008)
This paper shows that firms from financial centres are more likely to go public than their provincial counterparts. The financial centre bias is analysed for 32 countries, including the European Union, the USA and Japan. It is particularly strong in countries with underdeveloped stock markets and closed corporate governance regimes, but it is still present in countries with the most developed stock markets and most open corporate governance, such as the UK and the USA. Reasons for the bias include the benefits of issuers' proximity to IPO intermediaries and specialised labour markets, corporate governance incentives, and cultural factors.